Stables at Lanyon Homestead, Tharwa, Australian Capital Territory, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting rubble and stone building, corrugated-iron roofing, gravel courtyard.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions documentation, see file NLA09/703.
Wes Stacey reference number: 5 22 3.
Also available online
Published in: The Australian Homestead / by Philip Cox and Wesley Stacey. Melbourne : Lansdowne Press, 1972, p. 71.
Keywords: Lanyon Homestead (A.C.T.) -- Photographs; Stables -- Australian Capital Territory -- Tharwa -- Photographs; Stone buildings -- Australian Capital Territory -- Tharwa -- Photographs; Homesteads -- Australian Capital Territory -- Tharwa -- Photographs; Historic farms -- Australian Capital Territory -- Tharwa -- Photographs; Tharwa (A.C.T.) -- Buildings, structures, etc. -- Photographs